(2-z)(2z+5)=0

Simple and best practice solution for (2-z)(2z+5)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2-z)(2z+5)=0 equation:


Simplifying
(2 + -1z)(2z + 5) = 0

Reorder the terms:
(2 + -1z)(5 + 2z) = 0

Multiply (2 + -1z) * (5 + 2z)
(2(5 + 2z) + -1z * (5 + 2z)) = 0
((5 * 2 + 2z * 2) + -1z * (5 + 2z)) = 0
((10 + 4z) + -1z * (5 + 2z)) = 0
(10 + 4z + (5 * -1z + 2z * -1z)) = 0
(10 + 4z + (-5z + -2z2)) = 0

Combine like terms: 4z + -5z = -1z
(10 + -1z + -2z2) = 0

Solving
10 + -1z + -2z2 = 0

Solving for variable 'z'.

Factor a trinomial.
(2 + -1z)(5 + 2z) = 0

Subproblem 1

Set the factor '(2 + -1z)' equal to zero and attempt to solve: Simplifying 2 + -1z = 0 Solving 2 + -1z = 0 Move all terms containing z to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1z = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1z = 0 + -2 -1z = 0 + -2 Combine like terms: 0 + -2 = -2 -1z = -2 Divide each side by '-1'. z = 2 Simplifying z = 2

Subproblem 2

Set the factor '(5 + 2z)' equal to zero and attempt to solve: Simplifying 5 + 2z = 0 Solving 5 + 2z = 0 Move all terms containing z to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 2z = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 2z = 0 + -5 2z = 0 + -5 Combine like terms: 0 + -5 = -5 2z = -5 Divide each side by '2'. z = -2.5 Simplifying z = -2.5

Solution

z = {2, -2.5}

See similar equations:

| (t+33)+(t+11)=4t-9 | | 12-4y=6 | | s-4t=29 | | 4(6+2x)=2(x-3) | | 5(4-y)=20 | | 17-3x=2+3x | | 60-4t= | | y=-x^2-6x+4 | | s-4t= | | 1-2x=1-3y | | 3*0-4*y=6 | | 0.63+0.24t=2.68t-1.20 | | 33u-50+u+29=29u | | -8w^2+18w-9=0 | | 6(y-1)-4=-4(-6y+3)-4y | | 2y+2(y-8)=6y-4(y-10) | | 8x^2+16x=192 | | 39q+19+30=44q+45 | | 0=-16t^2+150t+30 | | x^2-49x+500=0 | | 6a-47+30=5a | | y+3-2(-8y-3)=7(y-1) | | 3.8x-4.7=3.8x+17.5 | | 19-12x=151 | | 2a+36=4a-14 | | 2.67x+3x=102 | | (x-2)2+(y-4)2=36expand | | 5x+10=-26 | | 34616.0131=B*45.3 | | ln(4x)+1=3 | | (v+39)+5v=11v-36 | | 3679.6530=171.9464*h |

Equations solver categories